The Essence of Modern Technologies in Teaching Vocabulary in EFL Classes (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Learning a language requires a good grasp of Vocabulary, which is crucial for effective communication. However, improving Vocabulary skills in the classroom has been a challenge. To address this issue, innovative technologies are being introduced to enhance vocabulary skills in students. Technology plays an important role in today's educational sector and offers use of effective tools for teaching Vocabulary skills such as the Internet, podcasts, video conferencing, videos and speech recognition software. This article explores innovative methods of Vocabulary activities and the use of technology to improve Vocabulary skills.